Test-Taking Performance of High School Students With ADHD. (January 2015) - Lewandowski, Lawrence; Hendricks, Kaitlin; Gordon, Michael
Objective: The authors examined the test-taking performance of high school students with ( n = 38) and without ( n = 746) ADHD.Method: Students were assessed via an online battery of tests (TestTracker) including reading speed, decoding, vocabulary, comprehension, effort, test anxiety, and time and strategy usage.Results: Students with ADHD had poorer decoding scores, and lower comprehension and vocabulary accuracy. Groups performed similarly on reading speed, number of items attempted, perceived test anxiety, self-perception of testing skills, and strategy use.Conclusion: Students with ADHD (all of whom were receiving test accommodations in school) made more errors on some reading tasks, yet performed similarly to typical students on indices of speed and amount of test items accessed. The finding of more errors but no time differences might argue for a different intervention beside extended time, unless the extra time is used to review and correct work.